An Assessment of the Causes of the Madhesh Movement 2015 - Dhakal, Sedunath (KMC Research Journal, 2018)
Conflict in a place is not caused by only a single factor. Many socio-economic, political and cultural factors are responsible to create a violent conflict. Nepal faced socio-political and regional conflict during the past decades, particularly after a decadelong Maoist insurgency had come to an end with peaceful resolution. The people’s movement 2062-63 overthrew the century-long monarchy system of governance, but there occurred different ethnic and regional movements for the identity and recognition. The Madhesh Movement of 2007 and 2015 were very remarkable for the socio-political changes in Nepal. There are many reasons behind Madhesh Movement 2015. This paper has analyzed the four major factors that caused the Madhesh Movement 2015, which are: (i) Poverty, Discrimination and Exploitation (ii) Exclusionary Nature of the State (iii) Influence of Ethnic Movements of Nepal in the Madhesh Movement 2015, and (iv)The Madhesh Movement for Identity. Although the movement occurred throughout Madhesh, four major conflict zones viz. Biratnagar, Janakpur, Birgunj, and Tikapur were taken as the research site. Owing to the same fact, this research paper is based on the response of the people from the conflict zones, experts’ opinions about the conflict, and the selected newspaper opinion articles during the major conflict period.